TELAAH TEORITIS STRUKTUR KEPEMILIKAN DALAM TEORI KEGENAN - TJANDRA, EILIEN (: 2303-1719)
Ownership structure is the composition of debt and equity. Given the ownership structure that contributed to the agency conflict. Agency conflict occurs because the separation between ownership and authority within the company, which require managers to do according to what is desired by the shareholder to shareholder wealth. Because of this, managers often take the opportunity that exists (opportunistic) to perform management of the company's earnings. Earnings management can occur due to gaps in information (information asymmetry) held between shareholders and managers. Agency conflict can be reduced by equity ownership structure, both managerial ownership and institutional ownership or other alternatives such as: the establishment of the board of directors, audit committees, GCG, dividend policy and debt policy. Agency conflict is not only happening in big firms, but in smaller companies like SMEs may also occur. For where the principal and the agent, then the conflict participated in it.